New data on the occurrence of two alien fishes, Pisodonophis semicinctus and Pomadasys stridens, from the Eastern Mediterranean Sea - BILECENOGLU, M.; KAYA, M.; ERYIGIT, A. (Mediterranean Marine Science, 2010)
The tropical Atlantic originated saddled snake eel, Pisodonophis semicinctus (Richardson, 1848) and the Indian Ocean originated striped piggy, Pomadasys stridens (Forsskål, 1775), are being recorded for the first time from Turkish coasts. First species is also a new addition to the eastern Mediterranean ichthyofauna, while the latter species has expanded its range to the northeastern Levant Sea.